The need for new metrics in the Anthropocene era - Vineis, Paolo; Mangone, Lorenzo (Frontiers in Public Health, 2022)
A limitation in the discussion concerning climate change is the large degree of separation between scientific, economic, and technological approaches to tackle the crisis. This issue is most noticeable when considering the lack of metrics to measure the impact of different productive sectors on both the environment and the health of the population. The best-known attempt to measure these repercussions has been the introduction of the Environmental, Social and Governance (ESG) ratings for bonds. However, this rating system suffers from a lack of transparency and standardization. Moreover, it does not offer insights on the health impact and the regenerative effort of the evaluated bonds. Thus, we think it is necessary to introduce new metrics, focusing on at least four dimensions: circularity, climate change, biodiversity and health (including well-being). A sector that needs a special consideration is that of energy. To better compare different energy sources, we propose to adjust metrics such as the Energy Return on Investment (EROI) or the energy intensity metrics to include the negative health effects and the environmental degradation associated with producing energy. A similar index of return on investment corrected for health impacts may be considered to evaluate food production as well. Hyper-analytical and extremely focused approaches have dominated the discussion around the environmental crisis. We believe that a more inclusive approach is now needed, to highlight the potential co-benefits of different strategies, especially those that promote regeneration and a truly circular economy.